Properties, Production and Applications of NiTi Shape Memory Alloy - Kristianova, Eva; Novak, Pavel (Manufacturing Technology Journal, 2015)
Approximately equiatomic alloy Ni-Ti is commercially most successful member of shape memory material group. This paper concludes basic knowledge about properties, ways of preparation and possible applications of this unique material in medicine, industry, construction or everyday life.
Keywords: NiTi; shape memory; properties; production